Implementasi Ajaran Bhakti Marga Yoga di Bali - Ida Bagus Subrahmaniam Saitya; Ni Luh Ratna Sari (Sphatika: Jurnal Teologi, 2021)
The existence of Banten in the religious activities of Hindus in Bali goes through a long history. In the Yajur Veda book, it is stated that there are offerings made to Gods as a manifestation of Brahman in the form of; gandam, ksatam, puspam, dupam, dipam, toyam, gretam, and soma. Meanwhile, in the Tantrayana teachings which are still very influential in Bali, it is stated that to show a sense of devotion to God one should carry out the concept of Panca Tattwa namely; matsya, mamsa, madhya, mudra, and maithuna. Both Vedic and Tantrayana teachings, and the local minds of the Balinese people, always underlie the offerings in the form of “offerings” which are packaged in symbols of human hope for God's manifestation. Hindus in Bali in practicing dharma bhakti to Him to God by using the means of offering can increase their faith and sradha bhaki and as an indicator of their longing identity.